2023
DOI: 10.1109/tdsc.2022.3186672
|View full text |Cite
|
Sign up to set email alerts
|

Preserving Privacy for Distributed Genome-Wide Analysis Against Identity Tracing Attacks

Abstract: Genome-wide analysis has demonstrated both health and social benefits. However, large scale sharing of such data may reveal sensitive information about individuals. One of the emerging challenges is identity tracing attack that exploits correlations among genomic data to reveal the identity of DNA samples. In this paper, we first demonstrate that the adversary can narrow down the sample's identity by detecting his/her genetic relatives and quantify such privacy threat by employing a Shannon entropy-based measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…Yet, despite a wide range of existing techniques for privacy-preserving GWAS analysis, including differential privacy, deep learning frameworks, and cryptographic technologies such as homomorphic encryption or secure multi-party computation, we are still so far from a generic framework, which may be applicable to genome-wide analysis, due to some inherent privacy and security risks [ 50 ]. Our review analysis revealed that most of the proposed privacy-preserving methods are limited to some statistics [ 20 ], as they do not cover all the GWAS tests [ 82 ].…”
Section: Discussion Challenges Visionmentioning
confidence: 99%
See 3 more Smart Citations
“…Yet, despite a wide range of existing techniques for privacy-preserving GWAS analysis, including differential privacy, deep learning frameworks, and cryptographic technologies such as homomorphic encryption or secure multi-party computation, we are still so far from a generic framework, which may be applicable to genome-wide analysis, due to some inherent privacy and security risks [ 50 ]. Our review analysis revealed that most of the proposed privacy-preserving methods are limited to some statistics [ 20 ], as they do not cover all the GWAS tests [ 82 ].…”
Section: Discussion Challenges Visionmentioning
confidence: 99%
“…Indeed, only a few studies can provide a correctness verification mechanism for the computation of the federated learning model [ 66 ]. Even worse is that only a limited number of studies have considered these threats in the GWAS context [ 50 ]. So far, verifying the integrity of the federated learning model and the correctness of the outcomes in an environment handled by intruders and attackers is not a trivial task [ 85 ], as the server does not have access to the dataset [ 59 ].…”
Section: Discussion Challenges Visionmentioning
confidence: 99%
See 2 more Smart Citations
“…Federated learning (FL) [1][2][3][4][5][6] is a cooperative machine learning technique that makes use of several clients (users) and a centralized server. Each client keeps track of its own private dataset, and only transfers its local parameter updates (gradient or weight) during iterative processes.…”
Section: Introductionmentioning
confidence: 99%